Monitoring sound levels in the intensive care unit: A mixed-methods system development project to optimize design features for a new electronic interface in the healthcare environment. (September 2021) - Darbyshire, Julie L.; Greig, Paul R.; Hinton, Lisa; Young, J. Duncan
Highlights: Understanding the user experience is key to effective design. Agile design practices foster efficient systems development. Implementing technological change requires socio-cultural understanding of teams. User-testing data from multiple sources allows for better systems evaluation. A well-designed system requires little training or explanation to use. Abstract: Background: Intensive care units (ICU) are busy round the clock and it is difficult to maintain low sound levels that support patient rest. To help ICU staff manage activities we developed a visual display that monitors and reports sound levels in real-time. This facilitates immediate feedback, encouraging proactive behavior change to limit disturbances. Methods: Following the principles of user-centered design practices we created our 'user persona' to understand the needs and goals of potential users of the system. We then conducted iterative user testing with current members of the ICU team, primarily using the 'think aloud' method to refine the design and functionality of our novel system. Ethnography evaluated team use of the display. Results: The final design was simple, clear, and efficient, and both functional and aesthetically pleasing for the key user demographic. We identified challenges in the implementation and adoption process that were separate from the 'usability' of the system itself. Conclusions: Embedding the design process within the core user demographic ensured the final product delivered relevant information for key users, and that this information was intuitive to interpret. Initiating sustainable change is not straightforward. It requires recognition of cultural practices within teams, departments, professions, organizations, and strategies to maximize engagement.